Peran Desa Adat Dalam Penanaman Modal Asing Di Provinsi Bali - Anak Agung Gede Arnawa; I Nyoman Putu Budiartha; Anak Agung Sagung Laksmi (Jurnal Analogi Hukum, 2025)
Indonesia is a country rich in customs and culture in each region and highly upholds the law based on the values of Pancasila and the 1945 Constitution. In human life, living independently is natural and cannot be denied. This fact can also be found in the life between countries (international interaction) mutual influence and interdependence of interests both economic, political defense and so forth is something essential. In this study there are two problem formulations including: 1) How is the position and function of indigenous villages towards foreign investment in Bali? 2) How is the legal regulation of indigenous villages against foreign investment? This research is a normative legal research based on laws and regulations and data obtained by the author on social media. The regulation of foreign investment in Indonesia is regulated based on Law No. 25 of 2007. This law contains a number of principles that underlie the formation of norms and rules contained in the articles of the Law.